Personal Data Protection in the Scope of Indonesian Law: Implications for the Act of Accessing Someone Else’s Mobile Phone - Hadiaty Y, Siti (International Journal of Humanities, Law, and Politics, 2024)
Personal data protection in Indonesia has become an important issue along with the development of information and communication technology. This study discusses the regulations governing personal data protection, specifically Law Number 27 of 2022 concerning Personal Data Protection (UU PDP), and its implications for police actions in accessing individual mobile phones. Using a literature study approach, this study identifies challenges faced in the implementation of data protection regulations, including the unclear principles of protection and the responsibilities of service providers. In addition, this study highlights the importance of proper procedures in police actions to protect individual privacy rights. The results of the study indicate that despite progress in regulations, challenges in implementation and public understanding still need to be overcome to ensure effective personal data protection.